Chiết tách axit (-)-hyđroxy xitric từ vỏ quả bứa bằng vi sóng. - Vinh, Đặng Quang; Cường, Đào Hùng; Thưởng, Nguyễn; Sang, Huỳnh (Vietnam Journal of Chemistry, 2012)
Surveys on the process of extracting acid from dried rinds of Garcinia oblongifolia Champ. ex Benth using microwave in terms of time, machine power and solid/liquid rate, have resulted in such findings as: the best time allocation for extracting is 25 minutes; machine power works best at level 2 (microwave power is 400W); suitable rate of solid/liquid is 0.071 (approximately 150 ml solvent per 10 g of sample). The total amounts acid and (-)-hydroxycitric acid extracted from 100g dried rinds of Garcinia oblongifolia Champ. ex Benth are 18.592 g and 10.137 g, respectively. This is the first finding on extraction of (-)-HCA from dried rinds of Garcinia oblongifolia Champ. ex Benth using microwave.